Impact of the interannual variability in autumn rainfalls on the biomass accumulation and botanical composition of temperate grassland (Semiárida, 2020)
The objective was to evaluate the incidence of the interannual variation of autumn rainfall on the structure and functionality of a grassland in the south west of Santa Fé During the autumn 2006 to 2012, in 850 hectares of natural grassland (Argiudol acuico, 18 sites), accumulated biomass (DM, kg ha-1) and the proportionality of each species were evaluated. Zavalla Meteorological Station (32°40' S; 61°17' W) provided information on rainfall, rainfall data of the study period were compared with the historical record. The data were subjected to a multivariate analysis of principal components (PC) using a correlation matrix and autumns as classification criteria. The first two CP explained 75% of the total variance. The species involved were important to define the structure and function of grassland. The CP1 ordered associating species with rainfall, and grouped in the wettest autumns to Trifolium repens, Loliun multiflorum, Paspalum dilatatum, graminoids and some compound, and Hordeum stenostachys, Stipa hyalina and S. neesiana in the less rainy. The second CP were related in 62% to P. dilatatum associated with the fall 2007, whose rains caused flooding temporary grassland, and in 68% to H. stenostachys associated with very dry autumns (2008 and 2009). The grassland showed a flexible behavior that allowed him to absorb the disturbances caused by the variability in autumn rainfall (average 248,24 mm ±117,11). There were marked changes and productive botanists caused by low rainfall that occurred in the autumn 2008 and 2009, these changes were reversed within three years after such extreme events. Over the autumns of transition to grassland recovery was observed a rapid reappearance of some productive species present in the previous situation.
Keywords: Temperate grassland; grassland structure; functionality of grassland; Autumn Rainfall